Investigation on Career Development, Work-Life Balance and Workplace Design Towards Millennials Work Engagement in India: Post-Pandemic Study - Hussain, Ibiwani Alisa; Singh, Sai Anurag (Electronic Journal of Business and Management, 2024)
The purpose of this paper is to examine the relationship between career development, work-life balance, and workplace design, with a particular focus on millennials’ work engagement. This study aimed to examine factors that engage millennial employees, who work in the private sector in India during the post-pandemic phase. A quantitative research design was used in this study and primary data were gathered using an online survey questionnaire. A random sampling method was adopted for data collection and 133 respondents were gathered. Findings revealed that while there is a positive relationship between millennial employee engagement with career development and workplace design, the association between work-life balance and millennial employee engagement was found to be insignificant. As the subject of study is still new, this study would contribute to the existing literature and the theories of millennial employee engagement in the Indian setting. It is, however, essential to note that the findings are based on limited responses and hence there cannot be any generalisation. Focusing on developing a strategy to promote engagement amongst employees at the workplace, especially after the post-pandemic amongst the millennials to enhance their work engagement.